2021
DOI: 10.1002/nau.24607
|View full text |Cite
|
Sign up to set email alerts
|

Bladder irrigation with povidone‐iodine prevent recurrent urinary tract infections in neurogenic bladder patients on clean intermittent catheterization

Abstract: Aims: To determine if daily povidone-iodine (PI) bladder irrigation in neurogenic lower urinary tract dysfunction (NLUTD) patients doing clean intermittent catheterization (CIC) can reduce the rate of symptomatic urinary tract infections (UTIs), emergency department (ED) visit for UTIs, and hospitalization for UTIs. Methods: We prospectively reviewed the records of patients with NLUTD on CIC who had recurrent symptomatic UTIs and who were placed on daily intravesical instillations of PI. This trial was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In this study, our prototype theranostic coatings were able to provide both advanced warning of catheter blockage as well as actively increasing the time taken for P. mirabilis to block catheters. While both therapeutic agents tested in our coatings may be administered orally for the treatment of UTIs, localized delivery options have the potential to avoid many of the systemic side effects associated with these drugs and provide a more effective way to combat CAUTIs (Benderev, 1988 ; Zacchè et al ., 2015 ; Wan et al ., 2018 ; Marei et al ., 2021 ; Moussa et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, our prototype theranostic coatings were able to provide both advanced warning of catheter blockage as well as actively increasing the time taken for P. mirabilis to block catheters. While both therapeutic agents tested in our coatings may be administered orally for the treatment of UTIs, localized delivery options have the potential to avoid many of the systemic side effects associated with these drugs and provide a more effective way to combat CAUTIs (Benderev, 1988 ; Zacchè et al ., 2015 ; Wan et al ., 2018 ; Marei et al ., 2021 ; Moussa et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a retrospective study found that intravesical gentamicin instillation reduced symptomatic UTI episodes, oral antibiotic use, and the proportion of resistant organisms. 78 Another study demonstrated that daily intravesical povidone-iodine bladder irrigation was associated with a significant reduction in symptomatic UTI in patients with neurogenic bladder and recurrent UTI who performed clean intermittent catheterization 79 Randomized clinical trials are needed to confirm these findings and determine whether they are generalizable to those with indwelling catheters.…”
Section: Dovepressmentioning
confidence: 99%
“…Currently, literature on the use of BWs in the management of recurrent UTIs is sparse. Evidence has demonstrated that bladder instillation without antibiotics has a role in preventing UTIs in catheterized patients [ 15 , 16 ]. Another study showed that BWs with an anti-septic solution are effective for treating catheter-associated UTIs [ 17 ].…”
Section: Introductionmentioning
confidence: 99%